2017
DOI: 10.1186/s13568-017-0503-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel yeast species Metschnikowia persimmonesis KCTC 12991BP (KIOM G15050 type strain) isolated from a medicinal plant, Korean persimmon calyx (Diospyros kaki Thumb)

Abstract: The yeast strain Metschnikowia persimmonesis Kang and Choi et al., sp. nov. [type strain KIOM_G15050 = Korean Collection for Type Cultures (KCTC) 12991BP] was isolated from the stalk of native persimmon cultivars (Diospyros kaki Thumb) obtained from different regions of South Korea and was characterized phenotypically, genetically, and physiologically. The isolate grew between 4 and 40 °C (optimum temperature: 24–28 °C), pH 3–8 (pH optimum = 6.0), and in 0–4% NaCl solution (with optimal growth in absence of Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
3
19
1
Order By: Relevance
“…The genus Metschnikowia was the most abundant within the class Saccharomycetes and also the most abundant in the majority of the sediments analyzed. The genus Metschnikowia comprises single-celled budding yeasts known for its participation in fermentation processes and wine production, reported mainly in terrestrial environments (Kang et al, 2017;Wang et al, 2017;Pawlikowska et al, 2019). There are few references to the presence of this genus in deep waters, although its presence had been previously reported in subtropical Chinese seas, including the southern and northern Yellow Sea and the Bohai Sea (Li et al, 2016), but with lower abundances than those reported in this study.…”
Section: Resultscontrasting
confidence: 45%
“…The genus Metschnikowia was the most abundant within the class Saccharomycetes and also the most abundant in the majority of the sediments analyzed. The genus Metschnikowia comprises single-celled budding yeasts known for its participation in fermentation processes and wine production, reported mainly in terrestrial environments (Kang et al, 2017;Wang et al, 2017;Pawlikowska et al, 2019). There are few references to the presence of this genus in deep waters, although its presence had been previously reported in subtropical Chinese seas, including the southern and northern Yellow Sea and the Bohai Sea (Li et al, 2016), but with lower abundances than those reported in this study.…”
Section: Resultscontrasting
confidence: 45%
“…Pulcherrimin-producing Metschnikowia strains are common components of the yeast communities that colonise ripening fruits, flowers (nectar), tree sap fluxes and also frequently occur in fruit juices and fermenting wine (e.g., [ 2 , 3 , 6 , 9 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]). New yeast isolates producing the characteristic maroon-red pulcherrimin halos around their colonies ( Figure 1 A) are frequently declared to belong to M. pulcherrima without taking into account that M. pulcherrima is not the only pigment-producing Metschnikowia species.…”
Section: Taxonomy Evolution and Taxonomic Identificationmentioning
confidence: 99%
“…persimmonesis and M. citriensis were proposed to accommodate pulcherrimin-producing strains. The taxonomic name M. persimmonesis was proposed for a single Korean isolate but without providing a complete taxonomic description [ 27 ]. The phylogenetic position of the strain is uncertain because its different rDNA barcode sequences (D1/D2, ITS and 18S) show the highest similarities to sequences of the type strains of different species.…”
Section: Taxonomy Evolution and Taxonomic Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Metschikowia was the most abundant within the class Saccharomycetes and also the most abundant in the majority of the sediments analyzed. The genus Metschikowia comprises single-celled budding yeasts known for its participation in fermentation processes and wine production, reported mainly in terrestrial environments (Kang et al, 2017; Wang et al, 2017; Pawlikowska et al, 2019). In this study, we showed that this fungal genus was present in a wide depth gradient, from 380 to 3474 m, indicating that it can be highly tolerant to gradients in temperature, dissolved oxygen, food supply, and the hydrostatic pressure associated with this change in depth.…”
Section: Resultsmentioning
confidence: 99%